Perubahan Sosial Ekonomi Masyarakat di Nagari Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung - Futi Sherly Asrilla; Nanik Rahmawati; Sri Wahyuni (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study discusses the livelihoods of the community in Nagari Tanjung Bonai Aur, with the background of the community experiencing a change in livelihood from rubber farmers moving to chicken farmers. Before moving to chicken farmers, initially the community had a livelihood as rubber farmers and became farmers on plantations. And when they became rubber farmers and plantation farmers, the economy was less stable, so people moved to chicken farmers. When you become a chicken farmer with a stable economy, your daily needs are more fulfilled than being a farmer and your children's education costs are met. The purpose of the research is to find out how the livelihood changes from rubber farmers to chicken farmers and to find out the level of community welfare in Nagari Tanjung Bonai Aur after the change in livelihood from rubber farmers to chicken farmers. This study used a descriptive qualitative method and purposive sampling in determining the informants with the steps of observation, interviews, and documentation as data collection techniques. The results of the study indicate that changes in livelihoods that occur in the community are due to several internal and external factors, internal factors which include changes in population, new discoveries. While external factors are natural factors. And when they become chicken breeders the economic life of the community is fulfilled and even increases, the need for their children's education can be met and when they become chicken breeders some of them are able to save money to carry out the pilgrimage. This was all because the community wanted to make changes in their lives and there was encouragement from other people related to the change in livelihood from rubber farmers to chicken farmers.